Respuesta :
Using the order of operations rule, the answer to 12 ÷ 2 + 4 – 2 × 3 = would be 4.
How? You would have to divide 12 by 2 to get 6, do 2 x 3 to get 6 again, then find the sum of 6 + 4 - 6, then you would end up with 10 - 6, and you would end up with 4.
Example:
12 ÷ 2 = 6
2 · 3 = 6
6 + 4 - 6
10 - 6
= 4.
How? You would have to divide 12 by 2 to get 6, do 2 x 3 to get 6 again, then find the sum of 6 + 4 - 6, then you would end up with 10 - 6, and you would end up with 4.
Example:
12 ÷ 2 = 6
2 · 3 = 6
6 + 4 - 6
10 - 6
= 4.